Mechanical Properties of Coconut Particle Board with Variation of Material Composition - Roni Jarlis (Universitas Syiah Kuala, 2022)
The research carried out is a laboratory experimental research withmake particle board from coconut coir, with variations in the composition of fibers and powders used are 100 % - 0%, 90 % - 10 %, 80 % - 20 %, and 70 % - 30 % using urea formaldehyde adhesive in order to determine the mechanical properties, and find a good composition of coconut coir particle board. Sampling was carried out at the Forestry Laboratory of the Muhammadiyah University of West Sumatra. The tests were carried out at the Civil Polytechnic Laboratory of Unand, and at the Agricultural Product Technology Laboratory of Unand. The independent variables in this study were thickness and composition variation. The dependent variable is density, flexural strength or MOR. Control variables are temperature, adhesive content, particleboard thickness, compression pressure, and drying time. Data were taken by repeated measurements of 5 samples. Based on the results of the research that has been carried out, it was found that the use of coconut coir powder particles as an outer coating for particleboard at different percentages has an influence on the mechanical properties of the particle board. From the results of the study, it was found that particleboard with a composition between fiber and coconut coir powder (90% - 10%) was the best result because the less powder used resulted in good mechanical properties with a density of 0.52 g/cm3 and flexural strength or MOR 159, 43 Kg/cm2.